AN EMPIRICAL STUDY ON THE INFLUENCING MECHANISMS OF SERVICE QUALITY, CUSTOMER SATISFACTION, AND BRAND IMAGE ON CUSTOMER LOYALTY - Ching-Kuo Wei (PEOPLE: International Journal of Social Sciences, 2025)
This study is an empirical investigation into the effects of service quality, customer satisfaction, and brand image on customer loyalty in high-end health management centers affiliated with medical centers in Taiwan, and to provide management strategy recommendations for healthcare institutions to enhance customer loyalty. A survey method was used, analyzing customers of high-end health management centers as the research subjects. A total of 500 questionnaires were distributed, with 446 valid samples collected. The questionnaire was reviewed by experts for expert validity, and the data met the required standards after reliability analysis. Statistical analysis was conducted on the questionnaire content to test the research hypotheses. Regarding demographic variables, age showed differences across all Dimension. Education level and monthly income showed significant differences in the loyalty construct. Customer satisfaction and brand image have a significant positive impact on customer loyalty, with customer satisfaction having a stronger influence. However, service quality did not have a direct significant impact on customer loyalty. Additionally, both service quality and brand image had a significant positive impact on customer satisfaction, indicating that service quality indirectly affects loyalty through customer satisfaction. It is worth noting that customers with a higher frequency of health checkups had lower loyalty. In the highly competitive health checkup service market, customer satisfaction and brand image are the key drivers of customer loyalty. Although basic service quality is a necessary condition, it does not directly affect loyalty. This suggests that customers take basic professionalism and service for granted. Therefore, if healthcare institutions can go beyond basic services by optimizing the process experience and building a professional yet humane brand image, it is recommended to shift the marketing focus from "quality promotion" to "brand value creation" to establish a long-term competitive advantage in the market.